Telomerase Reverse Transcriptase Promoter Mutations in Bladder Cancer: High Frequency Across Stages, Detection in Urine, and Lack of Association with Outcome - Allory, Yves; Beukers, Willemien; Sagrera, Ana; Flández, Marta; Marqués, Miriam; Márquez, Mirari; van der Keur, Kirstin A.; Dyrskjot, Lars; Lurkin, Irene; Vermeij, Marcel; Carrato, Alfredo; Lloreta, Josep; et al. (European urology, 2014)
Hotspot mutations in the promoter of the gene coding for telomerase reverse transcriptase (TERT) have been described and proposed to activate gene expression. To investigate TERT mutation frequency, spectrum, association with expression and clinical outcome, and potential for detection of recurrences in urine in patients with urothelial bladder cancer (UBC). A set of 111 UBCs of different stages was used to assess TERT promoter mutations by Sanger sequencing and TERT messenger RNA (mRNA) expression by reverse transcription-quantitative polymerase chain reaction. The two most frequent mutations were investigated, using a SNaPshot assay, in an independent set of 184 non–muscle-invasive and 173 muscle-invasive UBC (median follow-up: 53 mo and 21 mo, respectively). Voided urine from patients with suspicion of incident UBC (n=174), or under surveillance after diagnosis of non–muscle-invasive UBC (n=194), was tested using a SNaPshot assay. Association of mutation status with age, sex, tobacco, stage, grade, fibroblast growth factor receptor 3 (FGFR3) mutation, progression-free survival, disease-specific survival, and overall survival. In the two series, 78 of 111 (70%) and 283 of 357 (79%) tumors harbored TERT mutations, C228T being the most frequent substitution (83% for both series). TERT mutations were not associated with clinical or pathologic parameters, but were more frequent among FGFR3 mutant tumors (p=0.0002). There was no association between TERT mutations and mRNA expression (p=0.3). Mutations were not associated with clinical outcome. In urine, TERT mutations had 90% specificity in subjects with hematuria but no bladder tumor, and 73% in recurrence-free UBC patients. The sensitivity was 62% in incident and 42% in recurrent UBC. A limitation of the study is its retrospective nature. Somatic TERT promoter mutations are an early, highly prevalent genetic event in UBC and are not associated with TERT mRNA levels or disease outcomes. A SNaPshot assay in urine may help to detect UBC recurrences. Telomerase reverse transcriptase (TERT) promoter mutations are found in 70–80% of bladder tumors; their frequency is similar across stages. Mutations are not significantly associated with outcome. TERT mutations can be used to detect tumor cells in urine.